PEMANFAATAN LIMBAH PERTANIAN SEBAGAI PAKAN RUMINANSIA PADA PETERNAK RAKYAT DI KECAMATAN RENGAT BARAT KABUPATEN INDRAGIRI HULU - Dewi Febrina; Mairika Liana (State Islamic University of Sultan Syarif Kasim Riau, 2008)
The objective of this study was to evaluate characteristics of feeding management and utilization of crop residues at the animal husbandry system in Pematang Reba, Indragiri Hulu. Data were obtained through a survey and analyzed descriptively. The results of experiment indicated that animal raising system was mostly carried out in a traditional way (90%), in which animals freely during the day and tigh at night (80%), kept their animals only at night/semi intensive (7.5%) and freely during the day and kept their animal in cage at night (2.5%). The number of farmers who kept their animal in cage (intensive) was lower, i.e 10%. The percentage of farmers who utilized crop residues as feeding source was still low i.e 20%. There are not the farmers (0%) who knew about feeding technology and applied those technologies.